Pembunuhan Bayi Dalam Alquran Perspektif Mufassir Nusantara dan Dampaknya Terhadap Gangguan Kesehatan Mental - Wita, Rahma; Arifin, Zainal; Matondang, Husnel Anwar (Jayapangus Press, 2024)
Currently, many infanticides are carried out by their biological mothers, most of which are carried out in a planned manner. A mother is supposed to protect her baby, but this relationship is becoming less common nowadays. Many children receive bad treatment from their parents, even losing their lives. This research aims to explore infanticide in the Koran and analyze Indonesian interpreters' interpretations of the Koranic verses regarding infanticide and its impact on mental health disorders. This research uses qualitative methods with descriptive-analytic data analysis techniques. The results of this research show that murder is an act of taking human life. There are three words for murder in the Koran, namely, the word al-Qatl which totals 34 verses, the phrase al-Maut 1 verse, and the word fahisyah 8 verses. Furthermore, infanticide in the Koran, surah al-An'ām verse 151, and al-Isrā verse 31, according to Indonesian commentators, is the killing of girls for fear of poverty. Thus, the Koran has provided solutions to the factors that cause the murder of children, especially babies, so that this act can be avoided. In this case, Indonesian mufassir offers three solutions, namely giving alms, giving zakat, and abstaining from adultery. These three solutions have implementation for a person's mental health disorders, especially infanticide perpetrators who are worried about poverty.